Impact of early cleft lip and palate surgery on maxillary growth in 5- and 10-Year-old patients with unilateral cleft lip and palate: a cross-sectional study - Novakova, Magda; Brysova, Alena; Vokurkova, Jitka; Marcian, Petr; Borak, Libor; Koskova, Olga (BMC oral health, 2024)
OBJECTIVES: This study evaluated maxillary growth and dental arch relationships at 5 and 10 years of age in patients with unilateral cleft lip and palate (UCLP) who underwent early cleft lip and palate surgery. METHODS: 28 patients with UCLP who underwent cleft lip surgery in neonatal age and cleft palate surgery at average age of 7 months without orthodontic treatment (intervention group) were measured for intercanine and intermolar distances and for dental arch length. These measurements were compared with those of 30 healthy participants in a control group. Dental arch relationships in the intervention group were evaluated by 5-YO index at 5 years and the GOSLON Yardstick score at 10 years of patients' age. RESULTS: Patients in the intervention group had significantly shorter mean intercanine distance and arch length than control patients at both 5 and 10 years of age (p<.001 for all). There were no significant differences in intermolar distance at both 5 (p = .945) and 10 years (p = .105) of patients' age. The average 5YO index increased from 2.46 to an average GOSLON 10-year score of 2.89 in intervention group. CONCLUSION: Intercanine distance and dental arch length of patients with UCLP are significantly reduced at 5 and 10 years after early cleft lip and palate surgeries compared to the healthy population. Dental arch relationships at 5 and 10 years of patients with UCLP show comparable outcomes to those reported by other cleft centers. CLINICAL SIGNIFICANCE: This study evaluates maxillary growth in UCLP patients 5 and 10 years of age who underwent early primary lip and palate surgery.
Keywords: Cleft Palate; 5YO index; Female; Cleft Lip; předškolní dítě; dítě; GOSLON; ženské pohlaví; průřezové studie; lidé; rozštěp patra; studie případů a kontrol; rozštěp rtu; Cleft lip and palate; maxila; Cross-Sectional Studies; Male; Case-Control Studies; maxilofaciální vývoj; Maxillofacial Development; Child, Preschool; Dental arch relationship; Maxilla; Child; mužské pohlaví; Dental Arch; Neonatal cleft lip surgery; zubní oblouk; Humans